Experiences with an Innovative Approach to CAD/CAE System Teaching at Secondary Vocational Schools - Kuna, Peter; Haskova, Alena; Haller, Ján; Hrbáček, Jiří; Timor, Tsafi (Journal of Education Culture and Society, 2024)
Aim. In the paper the authors briefly describe a methodology they proposed to innovate engineering education at secondary vocational schools in the field of CAD/CAE systems, and subsequently in a more detail they analyse teachers´ experiences and opinions on the use of the proposed methodology, and to it designed teaching materials, in their teaching practice. Methods. The proposed innovative way of the CAD/CAE system teaching is based on inverting the ratio of the time allowance between teaching technical drawing, and teaching modelling and simulation from 2:1 to 1:2. The stated inverting enables on the one hand to reduce by half the number of teaching lessons allocated to creation of technical documentation, and on the other hand to double the number of teaching lessons devoted to modelling and simulations. Results. As a main output of the proposed innovative approach of the CAD/CAE system teaching two textbooks were created which can be used in teaching the subjects focused on technical drawing knowledge and skills acquisition at secondary vocational schools according to the newly proposed alternative way of teaching methodology of CAD/CAE systems. Conclusion. The created teaching materials supporting the teaching of CAD/CAE systems according to the proposed methodology undergone through an experimental implementation process at a selected sample of vocational schools in conditions of real pedagogical practice. Evaluation of the obtained experiences was done in a frame of a panel discussion.